Lateral Stresses on Retaining Wall Supporting Sandy Soil Under Dynamic Footing Loads - Aswad, Mohammed F.; Fattah, Mohammed Y.; Hamdi, Reham E. (Geotechnical and geological engineering, 2023)
Earth-retaining structures comprise an important subject in civil engineering researches, especially under dynamic loads. For the analysis and design of retaining walls in soils exposed to dynamic loads, accurate estimation of dynamic earth pressures and its point of application is very important. In this paper, the lateral stress distribution over the depth of the retaining wall on loose and dense sand under dynamic load on both active and passive sides was experimentally studied. A laboratory model of retaining wall supporting sandy soil was prepared. A footing was placed behind the wall and subjected to a dynamic load of harmonic half sine shape. It was found that the values of the active lateral stress decreased by increasing the sand relative density from 30 to 70% with keeping the other variables constant in all tests. On the other hand, in the passive side, the values increased by increasing the relative density from 30 to 70%. In both active and passive sides, all pressures collected revealed a nonlinear distribution with depth. In the active side, the position of the point of application is at height 0.56H (H is the wall height) and 0.54H for 30 and 70% relative density, while in the passive side, the elevations are 0.21H and 0.24H above the base of the wall for the both densities.